2013
DOI: 10.1111/1346-8138.12132
|View full text |Cite
|
Sign up to set email alerts
|

Acicular, but not globular, titanium dioxide nanoparticles stimulate keratinocytes to produce pro‐inflammatory cytokines

Abstract: Titanium dioxide (TiO2 ) nanoparticles, widely used for daily products, are believed to be biologically inert, but they may cause adverse effects on cells, presumably depending on the particle size and shape. One of the critical targets of TiO2 particles is epidermal keratinocytes, and their initial response to TiO2 may be production of pro-inflammatory cytokines. We therefore investigated the effects of four types of TiO2 particles on cytokine expression/production by real-time reverse transcription polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Although initial studies reported that TiO 2 did not penetrate the stratum corneum, a recent study indicated that the cubic and about 25nm size sample was cytotoxic to human epidermal keratinocytes 306 . Similarly, acicular TiO 2 ‐NP is shown to interact with human epidermal keratinocytes, induce secretion of pro‐inflammatory cytokines and disrupt the skin barrier by altering cell junctions 307 . The intestinal toxicity of NPs is less known, cationic liposome NPs containing ZnO, silver, aluminum, and nickel, as well as TiO 2 and SiO 2 NPs, accumulate across the intestinal epithelial barrier and then translocate by endocytosis by the M‐cell, or by disrupting the integrity of the cell membrane, or by phagocytosis by macrophages 305,308 .…”
Section: Environmental Substances Affecting the Epithelial Barriersmentioning
confidence: 99%
“…Although initial studies reported that TiO 2 did not penetrate the stratum corneum, a recent study indicated that the cubic and about 25nm size sample was cytotoxic to human epidermal keratinocytes 306 . Similarly, acicular TiO 2 ‐NP is shown to interact with human epidermal keratinocytes, induce secretion of pro‐inflammatory cytokines and disrupt the skin barrier by altering cell junctions 307 . The intestinal toxicity of NPs is less known, cationic liposome NPs containing ZnO, silver, aluminum, and nickel, as well as TiO 2 and SiO 2 NPs, accumulate across the intestinal epithelial barrier and then translocate by endocytosis by the M‐cell, or by disrupting the integrity of the cell membrane, or by phagocytosis by macrophages 305,308 .…”
Section: Environmental Substances Affecting the Epithelial Barriersmentioning
confidence: 99%
“…TiO 2 NPs can cause several adverse effects on mammalian cells, including ROS production [62,63], DNA damage responses [64], proliferation, and the induction of apoptosis [65,66]. Hiroike et al suggested that acicular, but not globular TiO 2 NPs stimulate keratinocytes to produce pro-inflammatory cytokines such as IL-1α, IL-1β, IL-6, TNF-α, and IL-8 [67]. The increased production of these cytokines leads to cutaneous inflammatory responses, as typically seen in contact dermatitis [68].…”
Section: Possible Role Of Inflammasome and Autophagy In Nanoparticmentioning
confidence: 99%
“…However, other immune cells such as dendritic cells or monocytes are also able to release large amount of mature IL-1β. In addition, structural cells of various body compartments exposed to particles secrete, although to a lesser extent, mature IL-1β [ 11 18 ]. For instance, primary rat epithelial lung cells, cardiomyocytes, cardiofibroblasts and mesothelial cells also respond to particles by priming and activating inflammasome [ 13 , 16 , 19 21 ].…”
Section: Introductionmentioning
confidence: 99%